STRUCTURAL CHANGES AND VALENCE STATES IN THE MGCR2O4-FECR2O4 SOLID SOLUTION SERIES - Lenaz D.; Princivalle F.; Skogby H.; Hålenius U. (My University, 2004)
The influence on the structure of Fe2+ → Mg substitution was studied in synthetic single crystals belonging to the MgCr2O4–FeCr2O4 series produced by flux growth at 900–1200 °C in controlled atmosphere. Samples were analyzed by single-crystal X-ray diffraction, electron microprobe analyses, optical absorption-, infrared- and Mössbauer spectroscopy. The Mössbauer data show that iron occurs almost exclusively as IVFe2+. Only minor Fe3+ (<0.005 apfu) was observed in samples with very low total Fe. Optical absorption spectra show that chromium with few exceptions is present as a trivalent cation at the octahedral site. Additional absorption bands attributable to Cr2+ and Cr3+ at the tetrahedral site are evident in spectra of end-member magnesiochromite and solid-solution crystals with low ferrous contents. Structural parameters a 0, u and T–O increase with chromite content, while the M–O bond distance remains nearly constant, with an average value equal to 1.995(1) Å corresponding to the Cr3+ octahedral bond distance. The ideal trend between cell parameter, T–O bond length and Fe2+ content (apfu) is described by the following linear relations: a 0=8.3325(5) + 0.0443(8)Fe2+ (Å) and T–O=1.9645(6) + 0.033(1)Fe2+ (Å) Consequently, Fe2+ and Mg tetrahedral bond lengths are equal to 1.998(1) Å and 1.965(1) Å, respectively.
Keywords: MgCr2O4; FeCr2O4; spinels; Single-crystal XRD; EPMA; OAS; Mossbauer